2006
DOI: 10.1080/09500340500147240
|View full text |Cite
|
Sign up to set email alerts
|

Coherent imaging with pseudo-thermal incoherent light

Abstract: We investigate experimentally fundamental properties of coherent ghost imaging using spatially incoherent beams generated from a pseudo-thermal source. A complementarity between the coherence of the beams and the correlation between them is demonstrated by showing a complementarity between ghost diffraction and ordinary diffraction patterns. In order for the ghost imaging scheme to work it is therefore crucial to have incoherent beams. The visibility of the information is shown for the ghost image to become be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(162 citation statements)
references
References 36 publications
5
157
0
Order By: Relevance
“…Ghost imaging and ghost diffraction of amplitude-only objects with classical thermal light have been examined experimentally [13,19,20,21,22,23,24,25] . Experimental evidence of Fresnel-transform ghost imaging and ghost diffractive imaging of a pure-phase object with both entangled photons and classical thermal light have also been reported [21,26], and the lenses are key optical elements in all these experiments.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Ghost imaging and ghost diffraction of amplitude-only objects with classical thermal light have been examined experimentally [13,19,20,21,22,23,24,25] . Experimental evidence of Fresnel-transform ghost imaging and ghost diffractive imaging of a pure-phase object with both entangled photons and classical thermal light have also been reported [21,26], and the lenses are key optical elements in all these experiments.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…The demonstrations of GI with classical light sources, and especially pseudothermal sources, triggered an ongoing e ort to implement GI for various sensing applications [4,7]. However, one of the main drawbacks of pseudothermal GI is the long acquisition times required for reconstructing images with a good signal-to-noise ratio (SNR) [1,8].In this work we propose an advanced reconstruction algorithm for pseudothermal GI, which reduces signicantly the required acquisition times. The algorithm is based on compressed sensing (or compressive sampling, CS) [9,10], an advanced sampling and reconstruction technique which has been recently implemented in several elds of imaging.…”
mentioning
confidence: 99%
“…Since the dark noise is independently and identically distributed in both y ′ odd and y ′ even , complementary CS can not only decrease the variance of the dark noise by half but also remove the impact of the other two kinds of noise (b object − and 0.5 a object + a+ a object − ), via Eq. (9). Although the complementary differential bucket signals seem to be a subtracted and rescaled version of those in conventional CS imaging, our method actually averages the variance of the noise, thus significantly improving the SNR in the measurement process.…”
Section: Performance and Discussionmentioning
confidence: 99%
“…The first demonstration of ghost imaging (GI) [1,2] utilized biphoton pairs which were produced by spontaneous parametric down conversion in a nonlinear crystal, hence the phenomenon was interpreted as the result of quantum entanglement of the photon pairs [3]. Subsequently, further theoretical and experimental work showed that GI is also achievable with pseudo-thermal [4][5][6][7][8][9][10] as well as true thermal light [11,12] and can be explained with a classical statistical model [13,14].…”
Section: Introductionmentioning
confidence: 99%